Future Changes in Maximum Temperature Events Using the Statistical Downscaling Model (SDSM) in Zlitan Area–Libya - Ibrahim, Abdussalam Ahmed Mohamed (المؤتمر العلمي الثاني لعلوم البيئة، 2015م, 2015)
In the 21st century, climate change is considered to be one of the greatest environmental threats to the world, and the changes in climate extremes are estimated to have greater negative impacts on human society and the natural environment than the changes in  mean  climate.All the IPCC's five reports between 1990 and 2013 concluded that we cannot expect stable climate in the future and we should prepare scenarios and strategies for the survival of humankind under the conditions of forthcoming global change.This study presents the projections of future changes in maximum temperature events under A2 and B2 SRES scenarios using the statistical downscaling model (SDSM) in the Zlitan Area–Libya. In order to explore the SDSM method, at Zlitan station in Libya has been selected as a study site to test the methodology for maximum temperature. The study included calibration and validate with large-scale atmospheric variables encompassing NCEP reanalysis data, the future estimation due to a climate scenario, which are HadCM3 A2 and HadCM3 B2 . Results of downscaling show that during the calibration and validation stage, the SDSM model can be well acceptable regard its performance in the downscaling of daily maximum temperature.The result of climate projection reveals that the SDSM model showed great reliability of SDSM in ascertaining changes for the periods 2011–2040, 2041–2070 and 2071–2099, relative to 1961–1990 and it has very good ability to replicate the historical maximum temperature for the observed period. Trend analysis in the study area showed an increase in average annual and monthly maximum temperature, compared to the baseline period for both HadCM3A2a and HadCM3B2a scenarios in both the dry and wet seasons.However, this increase is higher in dry months than wet months for all future time horizons and for both HadCM3A2a and HadCM3B2a scenarios. Thus there is likely to be a significant warming in local surface temperature, which is enough for a significant change on the energy balance and is likely to impact water availability.
Keywords: Statistical downscaling model; Intergovernmental Panel on Climate Change IPCC; Special Report on the Emission Scenarios